Disulfide bridge formation influences ligand recognition by the ATAD2 bromodomain. Issue 2 (27th December 2018) - Gay, Jamie C.; Eckenroth, Brian E.; Evans, Chiara M.; Langini, Cassiano; Carlson, Samuel; Lloyd, Jonathan T.; Caflisch, Amedeo; Glass, Karen C.
Abstract: The ATPase family, AAA domain‐containing protein 2 (ATAD2) has a C‐terminal bromodomain, which functions as a chromatin reader domain recognizing acetylated lysine on the histone tails within the nucleosome. ATAD2 is overexpressed in many cancers and its expression is correlated with poor patient outcomes, making it an attractive therapeutic target and potential biomarker. We solved the crystal structure of the ATAD2 bromodomain and found that it contains a disulfide bridge near the base of the acetyllysine binding pocket (Cys1057‐Cys1079). Site‐directed mutagenesis revealed that removal of a free C‐terminal cysteine (C1101) residue greatly improved the solubility of the ATAD2 bromodomain in vitro. Isothermal titration calorimetry experiments in combination with the Ellman's assay demonstrated that formation of an intramolecular disulfide bridge negatively impacts the ligand binding affinities and alters the thermodynamic parameters of the ATAD2 bromodomain interaction with a histone H4K5ac peptide as well as a small molecule bromodomain ligand. Molecular dynamics simulations indicate that the formation of the disulfide bridge in the ATAD2 bromodomain does not alter the structure of the folded state or flexibility of the acetyllysine binding pocket. However, consideration of this unique structural feature should be taken into account when examining ligand‐binding affinity, or in the design of new bromodomain inhibitor compounds that interact with this acetyllysine reader module.